2011
DOI: 10.1007/s10452-011-9372-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bacterial, ciliate and macroinvertebrate indicators of stream ecological health

Abstract: We evaluate the reliability of communities of bacteria and ciliated protozoa as indicators of freshwater ecological health. Samples of epilithic biofilm were taken from 18 freshwater streams, impacted by varying types and degrees of catchment modification. Communities of bacteria and ciliates were characterised using DNA fingerprinting techniques (automated ribosomal intergenic spacer analysis and terminal restriction fragment length polymorphism, respectively) and macroinvertebrate data also obtained, for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
3
21
2
Order By: Relevance
“…The bacterial community structure shifted with increasing urban land cover but with no impacts on alpha diversity assessed through relative diversity indices (OTU richness, Shannon index, evenness), as previously observed in other studies (Lear et al, ; Zeglin, ; Roberto et al, ). These results are in contrast with widely reported decreases in the diversity of ciliate, macroinvertebrate and fish communities in urban streams (Helms et al, ; Moore and Palmer, ; Lear et al, ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The bacterial community structure shifted with increasing urban land cover but with no impacts on alpha diversity assessed through relative diversity indices (OTU richness, Shannon index, evenness), as previously observed in other studies (Lear et al, ; Zeglin, ; Roberto et al, ). These results are in contrast with widely reported decreases in the diversity of ciliate, macroinvertebrate and fish communities in urban streams (Helms et al, ; Moore and Palmer, ; Lear et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…The bacterial community structure shifted with increasing urban land cover but with no impacts on alpha diversity assessed through relative diversity indices (OTU richness, Shannon index, evenness), as previously observed in other studies (Lear et al, 2011;Zeglin, 2015;Roberto et al, 2018). These results are in contrast with widely reported decreases in the diversity of ciliate, macroinvertebrate and fish communities in urban streams (Helms et al, 2005;Moore and Palmer, 2005;Lear et al, 2011). This finding is consistent with the hypothesis recently put forward by Hosen et al, (2017), who suggested that similar levels of bacterial diversity are maintained across the urbanization gradient because the introduction of novel bacterial taxa from sewage, water distribution or septic systems, and stormwater may compensate for the loss of taxa sensitive to urban conditions.…”
Section: Low Levels Of Watershed Urbanization Alter Sediment Bacteriasupporting
confidence: 82%
“…The average taxon richness of bacterial communities was observed to range from 177 OTUs (rural streams) to 194 OTUs (exotic forest), with native forest and urban streams having 184 and 185 OTUs, respectively. This is a key point of difference when compared with existing biological indicators such as macroinvertebrates, which are often depauperate in impacted streams, with the result that ecosystem assessments are forced to rely on a few 'tolerant' species (Boothroyd & Stark, 2000;Lear et al, 2011). The taxon richness of bacterial communities in these streams can be attributed to the inherent (or adapted) high tolerance of certain biofilm members to a wide range of environmental stressors such as pH, temperature, chemical composition including toxicant and heavy metal concentrations (Ager et al, 2010;Ancion, Lear & Lewis, 2010;Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, such metrics are generally limited to the analysis of communities of invertebrates (Boothroyd & Stark, ; Collier, ) and fish (Joy & Death, ). However, recent investigations of bacterial biofilm communities using modern molecular biology techniques suggest that these could offer an additional tool for assessing stream ecological health (Lear et al ., ; Vinten et al ., ). Bacterial biofilm communities have benefits as indicators since they provide responses to environmental stresses at the basal trophic levels that are detectable before the effects are relayed to upper layers of the stream ecosystem food web (Lewis & Turner, ; Lewis et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…This creates a paradox, whereby the locations where management interventions are undertaken in an effort to improve ecological health are the locations where detecting any improvement is challenging because of the limitations of existing biological indicators. In contrast, bacterial community diversity in impacted sites has been found to remain relatively high, with anthropogenic impact resulting in changes in bacterial community composition, but not a significant loss of diversity (Lear et al, 2011;Reis et al, 2013;Washington et al, 2013). The high bacterial diversity that is maintained even in highly degraded streams provides the potential for a sensitive biological indicator that can operate across the full range of impacted sites.…”
Section: Introductionmentioning
confidence: 99%